2021
DOI: 10.3389/fcvm.2021.712903
|View full text |Cite
|
Sign up to set email alerts
|

Bmal1 Downregulation Worsens Critical Limb Ischemia by Promoting Inflammation and Impairing Angiogenesis

Abstract: Critical limb ischemia (CLI) is the most advanced clinical stage of peripheral vascular disease with high mobility and mortality. CLI patients suffer from lower extremity rest pain, ulceration, and gangrene caused by insufficient blood and oxygen supply. Seeking for effective biomarkers and therapeutic targets is of great significance for improving the life quality of CLI patients. The circadian clock has been reported to be involved in the progression of kinds of cardiovascular diseases. Whether and how circa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Second, evidence showed that Bmal1 was associated with other ischemia‐related diseases such as myocardial infarction (Liu, Xiao, et al, 2021 ), stroke (Beker et al, 2018 ), and peripheral vascular disease (Xu et al, 2021 ), which are highly prevalent in aging populations (Hadjipanayi & Schilling, 2013 ); and some of these diseases have a close relationship with hypertension and atherosclerosis and may promote AD (Vijayan & Reddy, 2016 ; Zhang & Luo, 2020 ). There is an interesting link between vascular damage and Bmal1 deficiency when putting these diseases together, suggesting that a mechanism related to vascular pathology may be a common trigger.…”
Section: Summary and Discussion Of The Role And Mechanism Of ...mentioning
confidence: 99%
“…Second, evidence showed that Bmal1 was associated with other ischemia‐related diseases such as myocardial infarction (Liu, Xiao, et al, 2021 ), stroke (Beker et al, 2018 ), and peripheral vascular disease (Xu et al, 2021 ), which are highly prevalent in aging populations (Hadjipanayi & Schilling, 2013 ); and some of these diseases have a close relationship with hypertension and atherosclerosis and may promote AD (Vijayan & Reddy, 2016 ; Zhang & Luo, 2020 ). There is an interesting link between vascular damage and Bmal1 deficiency when putting these diseases together, suggesting that a mechanism related to vascular pathology may be a common trigger.…”
Section: Summary and Discussion Of The Role And Mechanism Of ...mentioning
confidence: 99%
“…As the core transcriptional factor, Bmal1 regulates the circadian pattern of downstream gene expression [49]. Besides this, Bmal1 has been shown to promote angiogenesis in ischemia-injured HUVECs (human umbilical vein endothelial cells) [50]. However, there is little evidence about the transcription function and epigenetic regulation of Bmal1.…”
Section: Discussionmentioning
confidence: 99%
“…As known downstream targets of the circadian clock network, VEGF protein displays the oscillation expression pattern, which is regulated by the core circadian component Bmal1, Clock, Per, and Cry genes ( Koyanagi et al, 2003 ). The overexpression of Bmal1 promotes the luciferase activity of VEGF; however, knocking down the VEGF expression reversed the promoting effects of Bmal1 in pro-angiogenesis in HUVECs Xu et al, (2021 ). The human VEGF promoter activity follows a 24-h circadian pattern under the 12 h light–dark (LD) cycle, and the core circadian gene Bmal1 plays a transcriptional role by targeting the region of the VEGF promoter ( Jensen et al, 2012 ).…”
Section: Circadian System In Angiogenesismentioning
confidence: 99%
“…In HUVECs, overexpression of Bmal1 promotes angiogenic activity, including proliferation, migration, and tube formation ability. Furthermore, in vitro research, Bmal1 −/− mice impaired angiogenesis by labeling CD31 and measuring the decreased VEGF protein level after peripheral ischemic injury ( Xu et al, 2021 ). Similarly, endothelial isolated from Per2 −/− mice substantially lost the vascular networks and proliferation ability, further contributing to increasing senescence ( Wang et al, 2008 ).…”
Section: Circadian System In Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation